PENGARUH PEMBERIAN AIR REBUSAN DAUN SAMBUNG NYAWA TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS BINANGA KECAMATAN BARUMUN TENGAH - Daulay, Nanda Masraini; Simamora, Febrina Angraini; Hidayah, Arinil (Universitas Aufa Royhan, 2024)
Hypertension cannot be cured but can be controlled so that it does not appear for a long time (years to decades) but still be watched out for. One of the medicinal plants that can be used as a herbal medicine for hypertension is the life-saving plant. The aim of this research is to determine the effect of giving boiled water from Sambung Nyawa leaves on reducing blood pressure in hypertension sufferers in the working area of the Binanga Community Health Center, Barumun Tengah District. This research design uses a quasi-experimental method. The population in this study were residents suffering from hypertension in the Binanga Community Health Center working area from January-December 2021, namely 198 people. The sampling technique in this research was a purposive sampling technique with a sample size of 22 people. The results of the research using the Wilcoxon statistical test showed that there was a significant influence between the effect of giving boiled water from splicing life leaves on reducing blood pressure in hypertension sufferers in the working area of the Binanga Community Health Center, Barumun Tengah District with a p-value = 0.000 (<0.05). The results of this study recommend that hypertension sufferers and their families are able to understand and comprehend the use of non-pharmacological therapy, namely boiled life-giving leaves as an alternative treatment for lowering blood pressure in hypertension sufferers. Keywords: life-giving leaves, blood pressure, hypertension